A Neo-Institutional Analysis of Corporate Governance Practices: Evidence from Bahrain - Al Jalahma, Abdulla (International Review of Management and Marketing, 2025)
This study explores corporate governance practices in Bahrain through the lens of Neo-Institutional Theory, focusing on the interactions between coercive, mimetic, and normative pressures. The study reveals the emergence of a hybrid governance model that integrates international standards with Bahrain’s distinct institutional and cultural context. Regulatory bodies have played a pivotal role in establishing robust governance frameworks, while Bahrain’s approach reflects a thoughtful alignment with global best practices—particularly Anglo-American models—combined with Shariah- based ethical principles. Increasing attention to Environmental, Social, and Governance (ESG) standards and sustainability confirmations Bahrain’s commitment to reform and international credibility. Through conducting semi-structured interviews with key stakeholders, the research sheds light on Bahrain’s strategic efforts to meet international governance expectations while addressing local priorities. The findings offer valuable guidance for policymakers, businesses, and emerging markets striving to strengthen corporate governance while preserving cultural identity.